The role of the robot mass and velocity in physical human-robot interaction - Part I: Non-constrained blunt impacts - Haddadin, S.; Albu-Schaffer, A.; Hirzinger, G. (2008 IEEE International Conference on Robotics and Automation, 2008)
The desired coexistence of robotic systems and humans in the same physical domain, by sharing their workspace and actually cooperating in a physical manner, poses the very fundamental problem of ensuring safety to the user. In this paper we will show the influence of robot mass and velocity during blunt unconstrained impacts with humans. Several robots with weights ranging from 15-2500 kg are impacted at different velocities with a mechanical human head mockup. This is used to measure the so-called head injury criterion, mainly a measure for brain injury. Apart from injuries indicated by this criterion and a detailed analysis of chest impacts we point out that e.g. fractures of facial bones can occur during collisions at typical robot velocities. Therefore, this injury mechanism which is more probable in robotics is evaluated in detail.